Fiberoptic monitoring of central venous oxygen saturation (PediaSat) in small children undergoing cardiac surgery: continuous is not continuous [v2; ref status: indexed, http://f1000r.es/394] - Francesca G. Iodice; Zaccaria Ricci; Roberta Haiberger; Isabella Favia; Paola Cogo (F1000Research, 2014)
Background: Monitoring of superior vena cava saturation (ScvO2) has become routine in the management of pediatric patients undergoing cardiac surgery. The objective of our study was to evaluate the correlation between continuous ScvO2 by the application of a fiber-optic oximetry catheter (PediaSat) and intermittent ScvO2 by using standard blood gas measurements. These results were compared to those obtained by cerebral near infrared spectroscopy (cNIRS). Setting: Tertiary pediatric cardiac intensive care unit (PCICU). Methods and main results: A retrospective study was conducted in consecutive patients who were monitored with a 4.5 or 5.5 F PediaSat catheter into the right internal jugular vein. An in vivo calibration was performed once the patient was transferred to the PCICU and re-calibration took place every 24 hours thereafter. Each patient had a NIRS placed on the forehead. Saturations were collected every 4 hours until extubation. Ten patients with a median age of 2.2 (0.13-8.5) years and a weight of 12.4 (3.9-24) kg were enrolled. Median sampling time was 32 (19-44) hours: 64 pairs of PediaSat and ScVO2 saturations showed a poor correlation (r=0.62, 95% CI 44-75; p<0.0001) and Bland Altman analysis for repeated measures showed an average difference of 0.34 with a standard deviation of 7,9 and 95% limits of agreement from -15 to 16. Thirty-six pairs of cNIRS and ScVO2 saturations showed a fair correlation (r=0.79, 95% CI 0.60-0.89; p<0.0001) an average difference of -1.4 with a standard deviation of 6 and 95% limits of agreement from -13 to 10. Analysis of median percentage differences between PediaSat and ScvO2 saturation over time revealed that, although not statistically significant, the change in percentage saturation differences was clinically relevant after the 8th hour from calibration (from -100 to +100%). Conclusion: PediaSat catheters showed unreliable performance in our cohort. It should be further investigated whether repeating calibrations every 8 hours may improve the accuracy of this system. CNIRS may provide similar results with a lower invasiveness.